ANALISIS KETETAPAN PENGADILAN AGAMA JAKARTA SELATAN TENTANG KEABSAHAN PERKAWINAN MELALUI MEDIA TELEPON - Sadiani, Sadiani (LP2M IAIN Palangka Raya, 2008)
This research to know the consideration punish the Justice of Religion of South Jakarta in making stipulating of marriage authenticity by phone and evaluate the positive law to consideration punish the religion justice in making stipulating of marriage authenticity by phone. Type of research of juridical normative about verdict of religion justice, while type of research of case study that is context of decision of marriage authenticity by phone the public versus opinion nature of research explanatory, explaining, strengthening, testing and even memo of theory or hypothesizing. Result of research that law consideration specified Justice of Religion of South Jakarta about marriage authenticity by phone to have the insufficiency seen from law method used and have implication to opinion object among jurist from Islam people, cause not mention the method punish the emergency in the balance punish. Law enforcement of marriage in perspective of positive law visible from juridical factor, valid marriage if noted or have got the justice decision; factor sociologies, applying right have to be elastic and flexible specially concerning technical marriage execution seemly is reality faced by the society; philosophic factor, applying right have to have the sense of justice and benefit ground and also express the system assess in society. The reality marriage by phone to represent one of opportunity of law renewal desired the pursuant to creativity of judge of religion justice to specify the marriage authenticity. Even method used in the balance punish still have the weakness, at least judge have coped to specify the marriage status by digging norm punish to answer the problem which not yet been arranged specifically in regulation.